The Knowledge and Attitudes of Pediatricians After Distance Education in The Early Period of The Covıd-19 Pandemic - Erdem Gönüllü (Çocuk Dergisi)
Objective: The COVID-19 epidemic started at the beginning of 2020, and has caused radical changes in life, work, and education. The possibility of breaking the educational efforts of affected healthcare workers at the center of the pandemic is a reality. The Pediatrics Atelier was established with the voluntary participation of pediatricians after graduation. A group of pediatricians made online cooperation and information sharing more systematic, and carried out practical information early in the COVID-19 epidemic. After the informative study, we planned a study to show the change created by distance education by evaluating the knowledge and attitudes of physicians. Material and Method: The demographic data of the group was determined with the online survey application made after the first online broadcast for this purpose. Results: Of the respondents (n=437), 146 (33%) were 28-35 years old, 171 (39%) were 36-44 years old, 109 (25%) were 45-60 years old, and 11 (3%) were over 61 years old. Of the participants who responded to the posttraining questionnaire, 279 (64%) were women. Forty-four (10%) of the survey participants were minor specialists. When the participants were asked from which source they got the information about COVID-19 before the training, 388 (88.7%) of them followed the information of the Ministry of Health, 204 (46.6%) of them followed the information of the World Health Organization, and 383 (87.6%) of them were Pediatrics. They stated that they followed the correspondence and programs of the workshop; 105 (24%) followed the literature via the Center for Disease Control (CDC) and 113 (25.8%) via PubMed. If the COVID-19 vaccine is offered, 323 (73.9%) of the participants have declared they would get the vaccine for themselves and their children, 58 (13.3%) said they would only get the vaccine for themselves, and 44 (10.1%) said would not get the vaccine for themselves or their children. Conclusion: Even in an unplanned and heterogeneous population, distance education can increase the knowledge level of the target group. Communities such as the Pediatrics Atelier can play a positive role, especially for the physician group whose access to information is asymmetrical due to geographical, economic, and unusual conditions.